2015
DOI: 10.1002/mds.26332
|View full text |Cite
|
Sign up to set email alerts
|

Basic science breaks through: New therapeutic advances in Parkinson's disease

Abstract: Parkinson's disease (PD) is the second most common neurodegenerative disease and is typically associated with progressive motor dysfunction, although PD patients also exhibit a variety of non-motor symptoms. The neuropathological hallmark of PD is intraneuronal inclusions containing primarily α-Synuclein (α-Syn), and several lines of evidence point to α-Syn as a key contributor to disease progression. Thus, basic research in the field of PD is largely focused on understanding the pathogenic properties of α-Syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…There are multiple reports showing that various therapies can attenuate αSyn pathology in transgenic mouse models (reviewed in [42]). However, only one previous report, using a peripherally administered monoclonal anti-αSyn antibody showed that prefibrillar αSyn aggregate induced α-synucleinopathy can be blocked in vivo [43].…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple reports showing that various therapies can attenuate αSyn pathology in transgenic mouse models (reviewed in [42]). However, only one previous report, using a peripherally administered monoclonal anti-αSyn antibody showed that prefibrillar αSyn aggregate induced α-synucleinopathy can be blocked in vivo [43].…”
Section: Discussionmentioning
confidence: 99%
“…It should be recognized that none of the currently available models of PD are perfect. However, it is fair to conclude that when these models, including most classic models, are used carefully, their contributions to our understanding of the neurobiology of PD and their role in promoting new therapies are phenomenal and clearly outweigh the shortcomings.…”
Section: The Present: Facts and Features Dr Parkinson Couldn't Envisagementioning
confidence: 99%
“…An alternative hypothesis is that the pathology in PD can be explained by intrinsic phenotypes of vulnerable neurons. The following 3 uncommon traits are shared by the small collection of neurons at risk in PD: long, highly branched axons with many alpha‐synuclein enriched vesicular release sites; autonomous pacemaking activity that triggers a pronounced elevation in cytosolic Ca 2+ concentration; and high basal mitochondrial oxidant stress . Each of these traits plays to the PD triumvirate.…”
Section: The Future: Unresolved Challenges and Developmentsmentioning
confidence: 99%
“…It is thus of utmost importance to find therapies to counteract the neurodegeneration and restore the neuronal circuits in the brain of PD patients. Previous research on pathophysiological processes in PD has also helped to identify novel and promising targets for neuroprotection (Brundin et al, 2015; Kalia et al, 2015; Lindholm et al, 2016). Unfortunately many novel molecules and trophic factors showing promising data in preclinical experiments and animal models of PD have failed to recapitulate these in more rigorous clinical trials (Kalia et al, 2015; Lindholm et al, 2016).…”
mentioning
confidence: 99%